Navigating the Transatlantic threshold: James Fenimore Cooper and the revolutionary Atlantic - Phair, Charles A.J. (2010)
This study aims to investigate the invention of the American sea novel by James Fenimore Cooper in the early nineteenth century and how this relates to the socio/political tensions within transatlatic relationships.